2019
DOI: 10.1186/s40738-019-0057-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes regarding elective oocyte cryopreservation in undergraduate and medical students

Abstract: Background To assess knowledge and attitudes regarding elective oocyte cryopreservation among female undergraduate students (UG) and medical students (MS) in Eastern Virginia. Methods An anonymous cross-sectional study surveying female UG at a local university and MS at our academic medical center in May of 2017. The survey contained questions on demographic information, interest in fertility preservation, and knowledge about age related changes in fertility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In this review, career advancement was not found to be a direct motivating factor in studies of known or potential OFNMR users 27,40,41,43 . However, from studies involving the general public, “career” was frequently cited as a reason to consider OFNMR 24,28‐30,32,36 . This includes two recent studies among student populations that identified career advancement to be a strong motivating factor to undergo OFNMR 24,32 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In this review, career advancement was not found to be a direct motivating factor in studies of known or potential OFNMR users 27,40,41,43 . However, from studies involving the general public, “career” was frequently cited as a reason to consider OFNMR 24,28‐30,32,36 . This includes two recent studies among student populations that identified career advancement to be a strong motivating factor to undergo OFNMR 24,32 .…”
Section: Discussionmentioning
confidence: 94%
“…Two studies, both evaluating American university students'/graduates' knowledge, reported that 33%‐56% of women had overly optimistic perceptions of age‐related fertility decline 18,21 . In Mahesan et al's study, 48% of students identified fertility decline to be greatest at age 36‐40 years 24 . Hickman et al's study reported that only 15% of women understood the likelihood of infertility at age 45 years 21 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other factors that are widely reported to influence motivations to undergo SEF include financial stability and career aspiration. Recent studies among student populations have identified career aspiration to be the most prevalent reason to undergo SEF, with 50.2%‐63% willing to consider it for this reason . However, these studies were undertaken in women in their early 20s, which is not reflective of the population who undergo SEF.…”
Section: Discussionmentioning
confidence: 99%